Does the management of anastomotic leakage after rectal cancer resection affect long-term oncological survival?: A retrospective propensity score-adjusted cohort study - Ammann, Yanic Rolf; Marti, Lukas; Warschkow, René; Bischofberger, Stephan; Reißfelder, Christoph; Schmied, Bruno; Brunner, Walter; Tarantino, Ignazio (Techniques in coloproctology, 2026)
Background The International Study Group of Rectal Cancer (ISREC) provides a classification of anastomotic leakage (AL). This classification categorises the severity of AL according to its clinical management. The aim of this study was to determine whether AL and its management influence survival. Methods Patients who underwent elective mesorectal excision (PME or TME) for primary rectal cancer stages I–III and who underwent anastomosis were included. A retrospective analysis of clinical data retrieved from a prospectively conducted database was performed. The primary endpoint was cancer-specific survival (CSS). Risk factors were adjusted by propensity score matching (PSM). The secondary endpoints were overall survival (OS), disease-free survival (DFS), and local recurrence-free rate (RFR). Results A total of 942 patients underwent surgery between 1991 and 2020 and were followed for a mean of 71.9 (SD 48.5) months. AL occurred in 141 patients (15.0%). Twenty-three patients had grade A AL (16.3%), 48 patients had grade B AL (34.0%), and 70 patients had grade C AL (49.6%). AL had no significant negative influence on the 5-year propensity score-adjusted survival rate for CSS (no AL 92.2%, AL 87.9%, p = 0.161), but did so on OS (no AL 78.6%, AL 66.9%, p = 0.005), DFS (no AL 72.9%, AL 60.9%, p = 0.011), and RFR (no AL 94.2%, AL 88.5%, p = 0.047). The severity of AL did not have a significant influence on CSS (p = 0.642). Conclusions AL had a negative influence on OS, DFS, and RFR. Whether aggressive surgical clinical management of AL has any influence on CSS remains unclear.